Amorphous NiFeMo oxide loaded on hollow hydrophobic cobalt-based carbon substrate and zinc air battery
By loading oteper Nifemo oxides and 酞 通过 iron on the cobalt -based carbon base, a new type of oxygen catalyst is formed, solving the problem of insufficient performance of traditional zinc air battery catalysts, and achieved efficient, low -cost zinc air batteries. Performance improvement.
Patent Information
- Application Number
- CN202411531724.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-30
- Publication Date
- 2025-01-21
AI Technical Summary
The cathode catalyst performance of traditional zinc air batteries is insufficient, affecting the overall efficiency and cycle life of the battery, and the high-cost platinum-based materials limit their large-scale commercial applications.
Amorphous NiFeMo oxide and iron phthalocyanine are dual-loaded on a hollow and carbon nanotube-rich cobalt-based carbon substrate to form a new oxygen electrocatalyst for the air cathode side of zinc-air batteries.
The catalytic performance, stability and durability of zinc-air batteries are significantly improved, achieving high peak power density and ultra-long stability, which is superior to the performance of commercial PtC and RuO2 catalysts.
Smart Images

Figure CN119340408A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of preparation of liquid rechargeable and dischargeable zinc-air batteries, and its air cathode side specifically relates to the technical field of preparation of new energy materials, and in particular to the technical field of electrocatalysis. Background Art
[0002] With the rapid depletion of fossil resources in recent years, new energy technologies have emerged in the 21st century. Among them, secondary batteries that can be charged and discharged and can be used multiple times have emerged in recent years and gradually occupied most of the world's new energy market. In this context, how to develop battery materials with high electrochemical activity, fast charging and discharging capabilities, and ultra-long stability has become a prominent and important topic in the battery field. Among them, zinc-air batteries have received widespread attention in recent years due to their high energy density and environmental protection characteristics. However, the practical application of zinc-air batteries still faces some technical challenges, among which the performance of cathode catalysts directly affects the overall efficiency and cycle life of the battery. Although traditional catalysts such as platinum-based materials have excellent catalytic activity, their high cost and resource scarcity limit their application in large-scale commercialization. Therefore, the development of new high-efficiency and low-cost catalysts for practical applications of zinc-air batteries has become a hot topic in current research.
[0003] The present invention proposes a novel cathode catalyst for liquid zinc-air batteries, which specifically adopts amorphous NiFeMo oxide and iron phthalocyanine to be double-loaded on a hollow cobalt-based carbon substrate rich in carbon nanotubes. The catalyst not only improves the catalytic performance of the zinc-air battery, but also enhances its stability and durability through reasonable material design and modification. Amorphous materials usually have high catalytic activity because their disordered structures can provide more active sites, and iron phthalocyanine, as an organic metal complex, has a unique molecular structure and electronic properties that give it high oxygen reduction activity. When the two are co-loaded on a cobalt-based nitrogen-doped carbon matrix, there is obvious electron transfer between the three, which synergistically optimizes the performance of a single species, thereby accelerating the electrochemical reaction kinetics of the battery, reducing overpotential, and improving the energy density and power output of the battery. The liquid zinc-air battery assembled with the catalyst as the cathode side catalyst of the zinc-air battery, a zinc sheet as the anode, and a 6 mol / L KOH solution + 0.2 mol / L zinc acetate solution as the electrolyte has high peak power density and ultra-long stability. Currently, few people can achieve such excellent performance on liquid zinc air. Summary of the invention
[0004] The invention relates to an oxygen electrocatalyst loaded with amorphous NiFeMo oxide and iron phthalocyanine (FePc) on a hollow hydrophobic cobalt-based nitrogen-doped carbon matrix. The zinc-air battery assembled with the oxygen electrocatalyst as the air cathode side has high peak power density and ultra-long stability. The technology promotes the development of zinc-air battery technology and provides new solutions for the storage and utilization of renewable energy. By loading different active species and constructing a cathode catalyst with good performance through the synergistic effect between different active species, the catalyst proposed by the invention can significantly improve the performance indicators of zinc-air batteries and promote their promotion and popularization in practical applications.
[0005] An oxygen electrocatalyst having amorphous NiFeMo oxide and iron phthalocyanine FePc supported on a hollow hydrophobic cobalt-based nitrogen-doped carbon matrix, wherein the XRD of the oxygen electrocatalyst substrate material includes characteristic peaks at about 26.3°, about 44.2°, 51.3°, and 75.7°, and these characteristic peaks include characteristic peaks of carbon and characteristic peaks of metallic cobalt (such as Figure 1 -A), the amorphous NiFeMo oxide has no obvious characteristic peaks in its XRD due to its disordered structure, showing an amorphous state (such as Figure 1 -B), when it is loaded on a cobalt-based nitrogen-doped carbon matrix, the original carbon peak and metallic cobalt peak are significantly weakened (as shown in Figure 1 -A), and then when iron phthalocyanine FePc is adsorbed thereon, due to the low content of FePc, there is no obvious characteristic peak in XRD.
[0006] The oxygen electrocatalyst is a hollow cubic structure, and the cubic shape has a concave structure; the hydrophobicity of the oxygen electrocatalyst is greater than 150°, and more preferably greater than 151°.
[0007] A method for preparing an oxygen electrocatalyst having amorphous NiFeMo oxide and iron phthalocyanine FePc loaded on a hollow hydrophobic cobalt-based nitrogen-doped carbon matrix comprises the following steps: The catalyst involved in the present invention has a preparation method as follows: Step S1: CCoNC preparation Cobalt nitrate hexahydrate, zinc nitrate hexahydrate, and CTAB are dissolved in deionized water to form solution A, and dimethylimidazole is dissolved in deionized water to form solution B. The two solutions are mixed and stirred, centrifuged, washed with methanol for multiple times, and dried. After complete drying, the prepared precursor is etched in a mixed solution of water and methanol containing tannic acid, centrifuged, washed with methanol for multiple times, and dried. Under a nitrogen atmosphere, the precursor etched with tannic acid is annealed by CVD to obtain CCoNC.
[0008] Among them, the concentration of cobalt salt in solution A is 23~24 g / L, the concentration of zinc salt is 5~6 g / L, and the concentration of CTAB is 0.4 g / L. In solution B, the concentration of dimethyl imidazole solution is 60~70 g / L, the tannic acid etching solution uses a mixed solution of water and methanol, the water-to-alcohol ratio is 1 / 1~1 / 5, the concentration of tannic acid in the water-to-alcohol solution is 10~15 g / L, the etching time is 10~15 min, the precursor annealing temperature is 800~1000℃, and the heating time is 5~10℃ / min.
[0009] Step S2: NiFeMo / CCoNC preparation CCoNC was ultrasonically dispersed in deionized water, and then molybdenum salt was added and ultrasonic dispersion was continued to form suspension C. Nickel salt and iron salt were dissolved in deionized water to form solution D. The two solutions were mixed and stirred at a certain temperature for a certain time, centrifuged, washed with methanol for multiple times, and dried.
[0010] Among them, the CCoNC content in suspension C is 1~1.5 g / L, and the ultrasonic dispersion time is 0.5~1 h. After adding sodium molybdate dihydrate, the concentration of sodium molybdate dihydrate in the suspension is 0.5~0.6 g / L, and the ultrasonic treatment is 5-10 min. The concentration of nickel salt in solution D is 5~6 g / L, and the concentration of iron salt is 2~3 g / L.
[0011] The molybdenum salt includes any one of sodium molybdate, potassium molybdate, and ammonium molybdate; the nickel salt includes any one of nickel nitrate, nickel chloride, and nickel sulfate; and the iron salt includes any one of iron nitrate, iron chloride, and iron sulfate.
[0012] Step S3: FePc@NiFeMo / CCoNC preparation The NiFeMo / CCoNC was ultrasonically dispersed in DMF to form a solution E. After being uniformly dispersed, iron phthalocyanine was added and ultrasonic dispersion was continued. After ultrasonic dispersion for a certain period of time, the solution was centrifuged, washed with DMF for multiple times, and dried.
[0013] The content of NiFeMo / CCoNC in solution E is 0.4-0.5 g / L, and the concentration of iron phthalocyanine in solution E is 0.05-0.07 g / L.
[0014] In step S3, the concentration of iron phthalocyanine in DMF is 0.05-0.07 g / L.
[0015] An oxygen reduction and oxygen evolution catalyst comprises the oxygen electrocatalyst or the oxygen electrocatalyst prepared by the method.
[0016] A liquid zinc-air battery comprises the oxygen electrocatalyst or the oxygen electrocatalyst prepared by the method. The zinc-air battery is composed of an air cathode, a zinc anode and an electrolyte. The FePc@NiFeMo / CCoNC catalyst on the air cathode side has excellent bifunctional activity and good hydrophobicity, and the liquid zinc-air battery assembled by preparing the catalyst on the air cathode side has high peak power density and cycle stability.
[0017] The FePc@NiFeMo / CCoNC electrocatalyst and preparation method involved in the present invention have the following significant features: FePc@NiFeMo / CCoNC composites outperform commercial PtC and RuO 2 The performance of the catalyst is superior to most electrocatalytic materials on the market. In addition to the excellent performance of its own catalytic species, its excellent performance is also due to the synergistic effect between iron phthalocyanine, amorphous NiFeMo and cobalt-based nitrogen-doped carbon matrix, which optimizes the catalytic activity of the three single catalytic species. At the same time, due to the cubic hollow structure of the cobalt-based nitrogen-doped carbon matrix, it provides a growth substrate for the growth of surface-rich carbon nanotubes, enhances the material's own conductivity and mass transfer capacity, and gives the material itself a good hydrophobic effect. The composite material has excellent catalytic activity, promotes the development of highly active catalysts, and enables it to be used in electrochemical energy devices.
[0018] The liquid zinc-air battery provided by the present invention is assembled with FePc@NiFeMo / CCoNC as the catalyst on the air cathode side, and the peak power density can reach 214 mW cm -2 , at 5 mA cm -2 After being able to operate stably for 2500h at a current density of , its charge and discharge gap did not increase significantly, showing excellent cycle tolerance. BRIEF DESCRIPTION OF THE DRAWINGS
[0019] Figure 1 XRD patterns of the samples prepared in Examples 1, 2, 3, 4, 5 and 6, A is the XRD of CCoNC, FePc@CCoNC, NiFeMo / CCoNC and FePc@NiFeMo / CCoNC; B is the XRD of NiFeMo and FePc@NiFeMo.
[0020] Figure 2 SEM images of samples prepared in Examples 1, 2, 3 and 4.
[0021] Figure 3 Hydrophobic angle test of Examples 1, 2 and 3.
[0022] Figure 4LSV curves of oxygen reduction of the samples prepared in Examples 1, 2, 3, 4, 5, and 6, as well as PtC and iron phthalocyanine. A is the oxygen reduction LSV curve of CCoNC, FePc@CCoNC, NiFeMo / CCoNC, FePc@NiFeMo / CCoNC, PtC, and FePc; B is the oxygen reduction LSV curve of NiFeMo and FePc@NiFeMo.
[0023] Figure 5 Color comparison of the supernatant after centrifugation in Examples 3 and 4 after loading with iron phthalocyanine.
[0024] Figure 6 The number of transferred electrons and the hydrogen peroxide yield of the samples prepared in Examples 1, 2, 3, 4, and 5, as well as PtC and iron phthalocyanine, A is the number of transferred electrons and the hydrogen peroxide yield of FePc@NiFeMo / CCoNC, FePc@CCoNC, CCoNC, and PtC; B is the number of transferred electrons and the hydrogen peroxide yield of NiFeMo / CCoNC, NiFeMo, and FePc.
[0025] Figure 7 Examples 1, 2, 3, 4, 5, 6 and RuO 2 LSV curves of oxygen evolution of the prepared samples, A is CCoNC, FePc@CCoNC, NiFeMo / CCoNC, FePc@NiFeMo / CCoNC, NiFeMo and RuO 2 A is the LSV curve of oxygen evolution; B is the LSV curve of oxygen evolution of NiFeMo and FePc@NiFeMo.
[0026] Figure 8 Example 3 and PtC / RuO 2 LSV curves before and after the ORR stability test, A is FePc@NiFeMo / CCoNC; B is PtC / RuO 2 .
[0027] Fig. 9 Example 3 and PtC / RuO 2 LSV curves after OER stability test, A is FePc@NiFeMo / CCoNC; B is PtC / RuO 2 .
[0028] Fig.10 Example 3 and PtC / RuO 2 The open circuit voltage and peak power density of FePc@NiFeMo / CCoNC and PtC / RuO2 are shown in Figure 2. A is the open circuit voltage of FePc@NiFeMo / CCoNC and PtC / RuO2; B is the open circuit voltage of FePc@NiFeMo / CCoNC and PtC / RuO 2 The peak power density.
[0029] Fig.11 Example 3 and PtC / RuO 2 At 5 mA cm -2 Constant current charge and discharge curves at current density. DETAILED DESCRIPTION
[0030] The specific embodiments of the present invention are described in detail below, but it should be understood that the protection scope of the present invention is not limited by the specific embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work belong to the protection scope of the present invention. The experimental methods described in the embodiments of the present invention are conventional methods unless otherwise specified.
[0031] The following experimental methods and detection methods, unless otherwise specified, are conventional methods; the following reagents and raw materials, unless otherwise specified, are commercially available.
[0032] The terms used in the present invention should be understood to be used to describe specific embodiments and should not be regarded as limiting the present invention. In addition, the numerical range described in the present invention should be understood to clearly disclose all intermediate values between the upper and lower limits of the scope. The intermediate value in any stated numerical value or numerical range, and each smaller range between any other numerical value or intermediate value in the described range are considered to be included in the scope of the present invention. The upper and lower limits of these smaller ranges can be independently and selectively included or excluded within the scope of the present invention.
[0033] At the same time, unless the context clearly requires otherwise, the words "include", "comprises" and similar words throughout the specification and claims should be interpreted as inclusive rather than exclusive or exhaustive; that is, the meaning is "including but not limited to".
[0034] The present invention is different from single-loaded composite catalysts. Most single-loaded composite catalysts can only maintain a single type of catalytic activity, including oxygen reduction or oxygen evolution performance. The dual-loaded composite catalyst can take into account dual-functional performance, and due to the synergistic effect between the composite catalytic species, the catalytic activity of the present invention is better than the catalytic activity of the single catalytic species itself.
[0035] Example 1 Step S1: Dissolve cobalt nitrate hexahydrate, zinc nitrate hexahydrate, and CTAB in deionized water to form solution A, with concentrations of 23-24 g / L, 5-6 g / L, and 0.4 g / L, respectively. Dissolve dimethylimidazole in deionized water to form solution B, with a concentration of 60-70 g / L. After the two solutions are stirred evenly, pour solution A into solution B and stir for 30-60 min. Centrifuge, wash with methanol several times, and dry to obtain CoZn-BZIF. Ultrasonic disperse the prepared CoZn-BZIF in methanol to form solution C. Dissolve tannic acid in deionized water to form solution D, and the concentration of tannic acid in solution D is 20 g / L. Quickly pour solution D into solution C, stir for 10 min, centrifuge, wash with methanol several times, and dry to obtain H-CoZn-BZIF. The prepared H-CoZn-BZIF was annealed with the aid of dicyandiamide, and the ratio of H-CoZn-BZIF to dicyandiamide was 1 / 1~1 / 3. In a protective atmosphere, the CCoNC was annealed at 800 °C for 2 h at a heating rate of 5 °C / min. Its XRD, SEM, hydrophobic angle, ORR / OER LSV, number of transferred electrons and hydrogen peroxide yield were shown as follows: Figure 1-4 , as shown in 6-7.
[0036] Example 2 Step S1: Dissolve cobalt nitrate hexahydrate, zinc nitrate hexahydrate, and CTAB in deionized water to form solution A, with concentrations of 23-24 g / L, 5-6 g / L, and 0.4 g / L, respectively. Dissolve dimethylimidazole in deionized water to form solution B, with a concentration of 60-70 g / L. After the two solutions are stirred evenly, pour solution A into solution B and stir for 30-60 min. Centrifuge, wash with methanol several times, and dry to obtain CoZn-BZIF. Ultrasonic disperse the prepared CoZn-BZIF in methanol to form solution C. Dissolve tannic acid in deionized water to form solution D, and the concentration of tannic acid in solution D is 20 g / L. Quickly pour solution D into solution C, stir for 10 min, centrifuge, wash with methanol several times, and dry to obtain H-CoZn-BZIF. The prepared H-CoZn-BZIF was annealed with the aid of dicyandiamide, and the ratio of H-CoZn-BZIF to dicyandiamide was 1 / 1~1 / 3. In a protective atmosphere, CCoNC was obtained by annealing at 800 ℃ for 2h at a heating rate of 5~10 ℃ / min. Its XRD, SEM, hydrophobic angle, ORR / OER LSV, number of transferred electrons and hydrogen peroxide yield are shown in Figure 2. Figure 1-4 , as shown in 6-7.
[0037] Step S2: Ultrasonic dispersion of CCoNC in deionized water to form suspension E, the content of which is 1~1.5 g / L, and the ultrasonic time is 1~2 h. Sodium molybdate dihydrate is added to suspension E, at which the concentration of sodium molybdate dihydrate is 0.5~0.6 g / L, and ultrasonication is continued for 10 min. Nickel nitrate hexahydrate and ferric nitrate nonahydrate are also dissolved in deionized water to form solution F, in which the concentration of nickel salt is 5~6 g / L and the concentration of iron salt is 2~3 g / L. Place the evenly dispersed suspension E on a water bath heating table, heat the water bath to 60°C, quickly pour solution F into suspension E, stir at a constant temperature for 1 h, centrifuge, wash with methanol several times, and dry to obtain NiFeMo / CCoNC. Its XRD, SEM, hydrophobic angle, ORR / OER LSV, number of transferred electrons and hydrogen peroxide yield are shown as follows: Figure 1-4 , as shown in 6-7.
[0038] Example 3 Step S1: Dissolve cobalt nitrate hexahydrate, zinc nitrate hexahydrate, and CTAB in deionized water to form solution A, with concentrations of 23-24 g / L, 5-6 g / L, and 0.4 g / L, respectively. Dissolve dimethylimidazole in deionized water to form solution B, with a concentration of 60-70 g / L. After the two solutions are stirred evenly, pour solution A into solution B and stir for 30-60 min. Centrifuge, wash with methanol several times, and dry to obtain CoZn-BZIF. Ultrasonic disperse the prepared CoZn-BZIF in methanol to form solution C. Dissolve tannic acid in deionized water to form solution D, and the concentration of tannic acid in solution D is 20 g / L. Quickly pour solution D into solution C, stir for 10-20 min, centrifuge, wash with methanol several times, and dry to obtain H-CoZn-BZIF. The prepared H-CoZn-BZIF was annealed with the aid of dicyandiamide, and the ratio of H-CoZn-BZIF to dicyandiamide was 1 / 1~1 / 3. In a protective atmosphere, CCoNC was obtained by annealing at 800 ℃ for 2 h at a heating rate of 5~10 ℃ / min. Its XRD, SEM, hydrophobic angle, ORR / OER LSV, number of transferred electrons and hydrogen peroxide yield are shown in Figure 2. Figure 1-4 , as shown in 6-7.
[0039] Step S2: Ultrasonic dispersion of CCoNC in deionized water to form suspension E, the content of which is 1~1.5 g / L, and the ultrasonic time is 1~2 h. Sodium molybdate dihydrate is added to suspension E, at which the concentration of sodium molybdate dihydrate is 0.5~0.6 g / L, and ultrasonication is continued for 10 min. Nickel nitrate hexahydrate and ferric nitrate nonahydrate are also dissolved in deionized water to form solution F, in which the concentration of nickel salt is 5~6 g / L and the concentration of iron salt is 2~3 g / L. Place the evenly dispersed suspension E on a water bath heating table, heat the water bath to 60°C, quickly pour solution F into suspension E, stir at a constant temperature for 1 h, centrifuge, wash with methanol several times, and dry to obtain NiFeMo / CCoNC. Its XRD, SEM, hydrophobic angle, ORR / OER LSV, number of transferred electrons and hydrogen peroxide yield are shown as follows: Figure 1-4 , as shown in 6-7.
[0040] Step S3: Ultrasonic dispersion of NiFeMo / CCoNC in DMF to form suspension G, with a content of 0.4-0.5 g / L, ultrasonic time of 1 h, adding phthalocyanine iron, at which point the concentration of phthalocyanine iron in suspension G is 0.05-0.07 g / L, and ultrasonication is continued for 2 h, centrifuged, washed with DMF for multiple times, and dried to obtain FePc@NiFeMo / CCoNC. Its XRD, SEM, hydrophobic angle, ORR / OER LSV, number of transferred electrons, and hydrogen peroxide yield are shown in Figure 3. Figure 1-4 , 6-7. The color of the supernatant after phthalocyanine iron adsorption is as follows Figure 5 The LSV curves after the ORR / OER stability test are shown as follows: Figure 8 , Fig. 9 Assemble it into a zinc-air battery Example 4 Step S1: Dissolve cobalt nitrate hexahydrate, zinc nitrate hexahydrate, and CTAB in deionized water to form solution A, with concentrations of 23-24 g / L, 5-6 g / L, and 0.4 g / L, respectively. Dissolve dimethyl imidazole in deionized water to form solution B, with a concentration of 60-70 g / L. After the two solutions are stirred evenly, pour solution A into solution B and stir at room temperature for 30 min. Centrifuge, wash with methanol several times, and dry to obtain CoZn-BZIF. Ultrasonic disperse the prepared CoZn-BZIF in methanol to form solution C. Dissolve tannic acid in deionized water to form solution D, and the concentration of tannic acid in solution D is 20 g / L. Quickly pour solution D into solution C, stir for 10 min, centrifuge, wash with methanol several times, and dry to obtain H-CoZn-BZIF. The prepared H-CoZn-BZIF was annealed with the aid of dicyandiamide, and the ratio of H-CoZn-BZIF to dicyandiamide was 1 / 1~1 / 3. In a protective atmosphere, the CCoNC was obtained by annealing at 800 °C for 2 h at a heating rate of 5 °C / min.
[0041] Step S2: Ultrasonic dispersion of CCoNC in DMF to form suspension G, with a content of 0.4-0.5 g / L, ultrasonic time of 1 h, adding iron phthalocyanine, at which point the concentration of iron phthalocyanine in suspension G is 0.05-0.07 g / L, ultrasonication for 2 h, centrifugation, DMF washing for multiple times, and drying to obtain FePc@CCoNC. Its XRD, SEM, hydrophobic angle, ORR / OER LSV, number of transferred electrons, and hydrogen peroxide yield are shown in Figure 2. Figure 1-4 , 6-7. The color of the supernatant after phthalocyanine iron adsorption is as follows Figure 5 shown.
[0042] Example 5 Step S1: Take sodium molybdate dihydrate and dissolve it in deionized water to form solution A, whose concentration is 0.5~0.6 g / L. Separately take nickel nitrate hexahydrate and ferric nitrate nonahydrate and dissolve them in deionized water to form solution B, in which the concentration of nickel salt is 5~6 g / L and the concentration of iron salt is 2~3 g / L. Place solution A on a water bath heating table, heat the water bath to 60 °C, quickly pour solution B into solution A, and stir for 1 h. Centrifuge, wash with methanol several times, and dry to obtain NiFeMo. Its XRD, ORR / OER LSV, number of transferred electrons and hydrogen peroxide yield are shown as follows: Figure 1 , 3 -4, 6-7.
[0043] Example 6 Step S1: Sodium molybdate dihydrate is dissolved in deionized water to form solution A, the concentration of which is 0.5-0.6 g / L. Nickel nitrate hexahydrate and ferric nitrate nonahydrate are dissolved in deionized water to form solution B, wherein the concentration of nickel salt is 5-6 g / L and the concentration of iron salt is 2-3 g / L. Solution A is placed on a water bath heating table, heated to 60 °C, and solution B is quickly poured into solution A, and stirred for 1 h. Centrifuge, wash with methanol several times, and dry to obtain NiFeMo.
[0044] Step S2: Take NiFeMo and disperse it in DMF by ultrasonic to form suspension C, whose content is 0.2~0.3 g / L, and the ultrasonic time is 1 h. Add iron phthalocyanine, and the concentration of iron phthalocyanine in suspension G is 0.05~0.07 g / L. Continue ultrasonication for 2 h, centrifuge, wash with DMF several times, and dry to obtain FePc@NiFeMo. Its XRD and ORR / OER LSV are as follows: Figure 1 , 4 , as shown in 7.
[0045] The catalyst prepared in the example was subjected to XRD test ( Figure 1 ), we found that Example 5 had no obvious characteristic peaks, indicating that the prepared NiFeMo all showed an amorphous morphology. The XRD of Example 1 showed obvious C peaks and metal Co peaks. Example 4 and Example 6 loaded iron phthalocyanine on Example 1 and Example 5, respectively. The XRD did not show the characteristic peaks of iron phthalocyanine, which we attributed to the low content of iron phthalocyanine. When NiFeMo was loaded on CCoNC, we found that the C peak and metal cobalt peak of CCoNC were significantly weakened, indicating that the amorphous NiFeMo was uniformly loaded on CCoNC, covering up the original characteristic peaks of CCoNC.
[0046] The catalysts prepared in Examples 1-4 were subjected to SEM testing ( Figure 2 ), we found that H-CoZn-BZIF etched with tannic acid and then carbonized at high temperature to obtain CCoNC can still maintain the cubic morphology, and the concave morphology of the cube indicates the successful etching of tannic acid, showing a hollow morphology. The abundant carbon nanotubes on the surface prove that the hollow cubic structure and CVD annealing promote the production of carbon nanotubes. The SEM image of Example 2 shows that NiFeMo assembled on CCoNC does not affect the overall morphological characteristics. The SEM image of Example 4 shows that phthalocyanine iron is loaded on CCoNC, which also does not affect the overall morphological characteristics. The SEM image of Example 3 shows that phthalocyanine iron and NiFeMo are dual-loaded on CCoNC, which also has little effect on the overall morphological characteristics.
[0047] The catalysts prepared in Examples 1-3 were tested for hydrophobic angles. There was no significant difference in the hydrophobic angles of Examples 1-3, indicating that the carbon nanotubes were not covered after loading, and abundant carbon nanotubes were still exposed on the surface, so that Example 3 still had excellent hydrophobic properties.
[0048] The catalyst prepared in the example was subjected to oxygen reduction LSV test ( Figure 4 ), the test structure shows that the double-loaded Example 3 has a better half-wave potential (0.903 V vs. RHE) than the other examples, and is better than the oxygen reduction performance of commercially applied PtC (0.863 V vs. RHE) and the single-loaded Example 4 (0.8978 V vs. RHE). Figure 5 It shows that the color of the supernatant after centrifugation of Example 3 and Example 4 after iron phthalocyanine loading changes from blue to green as the concentration of iron phthalocyanine in DMF decreases, proving the difference in the adsorption amount of the two. The adsorption amount of iron phthalocyanine on cobalt-based nitrogen-doped carbon exceeds the adsorption amount of cobalt-based nitrogen-doped carbon after single loading of amorphous NiFeMo oxide, proving that Example 3 after double loading has more excellent catalytic activity due to the synergistic effect between the three, and its intrinsic activity is higher.
[0049] Figure 6 It shows that the catalyst in Example 3 has a lower hydrogen peroxide yield (less than 5%) and is closer to a 4-electron transfer process.
[0050] The catalyst prepared in the example was subjected to LSV test for oxygen evolution ( Figure 7 ), the test results show that the double-loaded Example 3 has an -2 The current density is better than that of other examples and has a better oxygen evolution overpotential (267 mV) than that of commercially used RuO 2 (324 mV) has better oxygen evolution performance.
[0051] In the stability tests of oxygen reduction and oxygen evolution ( Figure 8-9 ), Example 3 has better performance than commercial PtC / RuO 2 Dual-function stability.
[0052] The dual-supported catalyst prepared in Example 3 was used as the positive electrode material to assemble a liquid zinc-air battery and then combined with commercially available PtC / RuO 2 For comparison ( Fig.10 The catalyst prepared in Example 3 has a higher open circuit voltage (1.49 V) and a higher peak power density (214 mW cm -2 ), significantly better than PtC / RuO 2(1.45 V and 173 mW cm -2 ). And in the long-cycle stability test, 5 mA cm -2 At a current density of , the catalyst prepared in Example 3 can stably operate for 2500 h ( Fig.11 ), its voltage gap did not change significantly, which was significantly better than PtC / RuO 2 .
Claims
1. An oxygen electrocatalyst comprising amorphous NiFeMo oxide and iron phthalocyanine FePc supported on a hollow hydrophobic cobalt-based nitrogen-doped carbon matrix, characterized in that: The XRD of the oxygen electrocatalyst substrate material includes characteristic peaks at about 26.3°, about 44.2°, about 51.3°, and about 75.7°.
2. The oxygen electrocatalyst according to claim 1, characterized in that The oxygen electrocatalyst is a hollow cubic structure, and the cubic shape has a concave structure; the hydrophobicity of the oxygen electrocatalyst is greater than 150°.
3. A method for preparing an oxygen electrocatalyst having amorphous NiFeMo oxide and iron phthalocyanine FePc supported on a hollow hydrophobic cobalt-based nitrogen-doped carbon matrix, characterized in that: The steps include: Step S1, preparing CCoNC: taking a certain amount of cobalt salt, zinc salt, and CTAB and dissolving them in water, adding a dimethyl imidazole aqueous solution to carry out stirring reaction; after the reaction, centrifuging, washing, and drying, adding tannic acid to carry out etching, and after etching, washing, drying, and deannealing to obtain CCoNC; Step S2, preparing NiFeMo / CCoNC: taking a certain amount of CCoNC and dispersing it in deionized water by ultrasonic, adding a certain amount of molybdenum salt, and ultrasonically dispersing it until it is uniform, and then adding nickel salt and iron salt solution, and reacting under heating and stirring, and the obtained product is centrifuged, washed, and dried to obtain NiFeMo / CCoNC; Step S3, preparation of FePc@NiFeMo / CCoNC: taking a certain amount of NiFeMo / CCoNC and ultrasonically dispersing it in N,N-dimethylformamide, after it is evenly dispersed, adding a certain amount of iron phthalocyanine, continuing ultrasonic dispersion for a certain time, centrifuging, washing with DMF for multiple times, and drying.
4. The preparation method according to claim 3, characterized in that: In step S1, the concentrations of the cobalt salt, zinc salt and CTAB aqueous solution are 23-24 g / L, 5-6 g / L and 0.3-0.6 g / L respectively; The concentration of the dimethylimidazole aqueous solution is 60~70 g / L.
5. The preparation method according to claim 3, characterized in that: In step S1, the tannic acid etching solution is a mixed solution of water and methanol, with a water-to-methanol ratio of 1 / 1-1 / 5, and a tannic acid concentration in the water-to-methanol solution of 10-15 g / L.
6. The preparation method according to claim 3, characterized in that: In step S1, the annealing temperature is 800-1000° C. and the annealing time is 2-4 hours.
7. The preparation method according to claim 3, characterized in that: In step S2, the mass ratio of CCoNC to molybdenum salt is 5-10:1-3; the concentration of nickel salt and iron salt solution is 7-8 g / L; The molybdenum salt includes any one of sodium molybdate, potassium molybdate, and ammonium molybdate; the nickel salt includes any one of nickel nitrate, nickel chloride, and nickel sulfate; and the iron salt includes any one of iron nitrate, iron chloride, and iron sulfate.
8. The preparation method according to claim 3, characterized in that: In step S3, the concentration of iron phthalocyanine in DMF is 0.05-0.07 g / L.
9. An oxygen reduction and oxygen evolution catalyst, characterized in that It comprises the oxygen electrocatalyst according to claim 1 or 2, or the oxygen electrocatalyst prepared by the method according to any one of claims 3-8.
10. A liquid zinc-air battery, characterized in that: It comprises the oxygen electrocatalyst according to claim 1 or 2, or the oxygen electrocatalyst prepared by the method according to any one of claims 3-8.